IDENTIFICATION OF CHARACTERISTIC FEATURES OF THE FUNCTIONING OF TERMS AND WAYS OF THEIR TRANSLATION BASED ON THE MATERIAL OF TEXTS ON MANAGEMENT (Novateur Publications, 2023)
The monograph examines the terminological system of texts on management and cross-culture, since, it seems, the structural features of terms in such texts may reflect the degree of terminology and modern common vocabulary, as well as a wide range of functioning of various terms. After all, terminology, in our opinion, forms a certain linguistic layer, without which business communication is impossible.The issue of specificity of terminology and the difficulty of translating terms has always occupied a special place in linguistics. The proof is a lot of articles, research papers and monographs devoted to terminology.